Eça Naturalista: O Crime do Padre Amaro e O Primo Basílio na imprensa coeva - António Apolinário Lourenço (Documentos, 2019)
This book examines the reception of the first two novels by Eça de Queirós, which introduced naturalistic aesthetics in Portugal. Without entirely breaking away from Balzacian realism, Émile Zola, in his saga of the Rougon-Macquart, established a set of technical narrative procedures, imported from Flaubert's Madame Bovary, which would define the prevailing poetics of the novel in Europe until the end of the 1880s. Eça's early adoption of these rules (namely narrative impersonality, internal characterization and free indirect speech), first in O Crime do Padre Amaro and later in O Primo Basílio, make the Portuguese writer the first naturalist novelist outside French territory. The theoretical and critical reflection on the Portuguese naturalist movement is accompanied by the reproduction of the main pieces published in the Portuguese press on these Queirosian novels.